2000
DOI: 10.1128/jvi.74.22.10274-10286.2000
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Adenovirus Infectivity on Length of the Fiber Shaft Domain

Abstract: One of the objectives in adenovirus (Ad) vector development is to target gene delivery to specific cell types. Major attention has been given to modification of the Ad fiber knob, which is thought to determine virus tropism. However, among the human Ad serotypes with different tissue tropisms, not only the knob but also the length of the fiber shaft domain varies significantly. In this study we attempted to delineate the role of fiber length in coxsackievirus-adenovirus receptor (CAR)-and non-CAR-mediated infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
168
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(179 citation statements)
references
References 70 publications
(62 reference statements)
10
168
0
1
Order By: Relevance
“…This may be because the HAd37 fiber shaft is too short and rigid to allow efficient binding to cellular CAR when the fiber is attached to the virus (38). Other studies also confirm that the length and flexibility of the fiber shaft is critical in infectivity (39).…”
mentioning
confidence: 66%
“…This may be because the HAd37 fiber shaft is too short and rigid to allow efficient binding to cellular CAR when the fiber is attached to the virus (38). Other studies also confirm that the length and flexibility of the fiber shaft is critical in infectivity (39).…”
mentioning
confidence: 66%
“…The crucial role played by fiber and knob proteins of the virus in transduction prompts the genetic modification of these proteins. Studies have shown that transduction efficiency of the virus has shown dependency on the length of the fiber protein (Legrand, Spehner et al 1999;Shayakhmetov and Lieber 2000;Vigne, Dedieu et al 2003). Further, complete removal of the knob domain has been established as a way to 54 ablate tropism (Magnusson, Hong et al 2001).…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Human reovirus T3D was kindly provided by Terence Dermody (Vanderbilt University, Nashville, TN). Viruses were banded in CsCl gradients, dialyzed, and stored in aliquots, as described (34). Adenovirus genome titers were determined by quantitative real-time PCR (for Ad5RFP and Ad5BAP) and OD260 measurement (for wildtype viruses).…”
Section: Methodsmentioning
confidence: 99%
“…An Ad5-FX complex was prepared by mixing 100 l of the Ad5S vector (34), which has a short-shafted fiber (1 ϫ 10 13 virus particles per ml) with 1 l of FX (2 mg/ml). Six-microliter aliquots of the Ad5-FX complex were applied to Quantifoil R2/4 holey carbon grids (Quantifoil Micro Tools) and a Vitrobot cryofixation device (FEI) was used for blotting and sample vitrification in liquid ethane.…”
Section: Cryoelectronmentioning
confidence: 99%